2021
DOI: 10.1021/acs.joc.0c02729
|View full text |Cite
|
Sign up to set email alerts
|

Reducing-Agent-Free Convergent Synthesis of Hydroxyimino-Decorated Tetracyclic Fused Cinnolines via RhIII-Catalyzed Annulation Using Nitroolefins

Abstract: A mild Rh-catalyzed method was developed for the synthesis of hydroxyimino functionalized indazolo[1,2-a]cinnolines and phthalazino[2,3-a]cinnolines by reductive [4 + 2] annulation between 1-arylindazolones and 2-aryl-2,3-dihydrophthalazine-1,4diones with varied nitroolefins. The targeted oxime decorated tetracyclic fused cinnolines were synthesized via sequential C−H activation/olefin insertion/reduction under reducing-agent-free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Based on our mechanistic studies and the previous literature, 7–10 we proposed a plausible catalytic cycle as shown in Scheme 5. The active catalyst Cp*M( iii ) species I is generated from [Cp*MCl 2 ] 2 , AgSbF 6 and an additive by a ligand exchange, and I reacted with the substrate 1 to give metal complex II by a concerted metalation–deprotonation (CMD) process.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Based on our mechanistic studies and the previous literature, 7–10 we proposed a plausible catalytic cycle as shown in Scheme 5. The active catalyst Cp*M( iii ) species I is generated from [Cp*MCl 2 ] 2 , AgSbF 6 and an additive by a ligand exchange, and I reacted with the substrate 1 to give metal complex II by a concerted metalation–deprotonation (CMD) process.…”
mentioning
confidence: 77%
“…5 Besides, there are only several examples of group 9 Cp*M( iii )-catalysed C–H activation/cascade annulations for heterocyclic compound synthesis. For instance, one category is the formal [4 + 1] annulation reaction between 1-arylindazolones and C1 synthons (maleimides); 6 another type is the [4 + 2] annulation between 1-arylindazolones and C2 synthons such as alkynes, 7 nitroolefins 8 and iodonium ylides (Scheme 1a). 9 However, poor substrate scope and harsh reaction conditions may limit their applications in the realm of heterocyclic synthesis.…”
mentioning
confidence: 99%
“…Phthalazine is one such diazaheterocyclic moiety of paramount importance that has displayed an interesting pharmacological profile, and its derivatives have exhibited anti-inflammatory, 5 antitumor, 6 antihypertensive, 7 antimicrobial 8 and anticonvulsant activities. 9 Using the above highlighted DG-aided functionalization notion, powerful methods have been developed in recent times for the annulation of N -phenyl-2,3-dihydrophthalazine-diones with varied coupling partners, including isocyanates, 10 nitroolefins, 11 propargyl alcohols, 12 alkynes, 13 allenes, 14 sulfoxonium ylides 15 and α-diazo compounds 16 via transition-metal catalysis. However, the synthesis of (spiro)annulative products with N -aryl-2,3-dihydrophthalazine-diones has been explored only to a limited extent.…”
Section: Introductionmentioning
confidence: 99%
“…In this realm, atom-economical approaches to fused-phthalazinones, ,, pyrazolones, , and indazolones ,, have been developed through TM-catalyzed directing group (DG)-assisted C–H/N–H annulations. Furthermore, [4 + 2] annulation of 1-aryl/2-arylindazolones with acetylenes, α-diazo carbonyls, , and β-nitrostyrenes have been realized toward the construction of cinnoline-fused indazolones under Ru II , Ir I , and Rh III catalysis (Scheme ).…”
mentioning
confidence: 99%
“…In striking contrast, allenes have emerged as a valuable coupling partner for allylation, alkenylation, and annulation a , , of electron-rich arenes under metal catalysis at the expense of an appropriately attached amidic directing group (DG). However, the presence of three reactive carbon centers in substituted allenes unveils complex reactivity patterns based on steric and electronic properties of the attached substituents, furnishing five- and/or six-membered annulated products; the regioselective generation of these remains a challenging task.…”
mentioning
confidence: 99%